Treatment Outcome of Drug Resistance Tuberculosis From a Centre of Eastern Region, Nepal - Ghimire, H.B.; Rimal, H.S.; Parajuli, P. (Birat Journal of Health Sciences, 2017)
Introduction Drug resistance tuberculosis (DRTB) has become major problem worldwide with difficulty in treatment. Objective The study is conducted to find the incidence and outcomes of DRTB in one of the eastern tuberculosis treatment centre of Nepal. Methodology We collected all the cases of DRTB being treated from national anti-tuberculosis association of Biratnagar, Nepal. There were altogether 154 patients, who had sputum culture with resistance of at least one anti tubercular drug (ATD), included in this study. Results Of 154 total patients, 36 patients were resistant to rifampicin only, 84 patients were resistant to isoniazid and rifampicin, 18 patients were resistant to isoniazid, rifampicin and ethambutol and 16 patients were resistant to isoniazid, rifampicin and either streptomycin or fluoroquinolone. There was overall 71% cure rate in case of drug resistance tuberculosis. There was only statistical difference between cured and died patients in case of sputum conversion time with earlier sputum conversion in cured patients. Similarly, patients who were previously treated with category 2 ATD had only resistance to ethambutol or streptomycin or fluoroquinolone besides resistance to isoniazid and rifampicin compared to new patients and patients treated with category 1 regimen; as these groups were not found to be resistant to first three drugs. Conclusion There was overall 71% cure rate in case of drug resistance tuberculosis. Earlier sputum conversion was seen in cured patients compared to those who died during the treatment. Multiple drugs were resistant in patients previously treated with category 2 Anti-tubercular drugs. Birat Journal of Health Sciences 2016 1(1): 20-26